2020
DOI: 10.1016/j.mayocp.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Update on Treatment of Clostridioides difficile Infection

Abstract: Clostridioides difficile infection (CDI) is the leading cause of health careeassociated infections in the United States. The increasing incidence and recurrence rates of CDI together with its associated morbidity and mortality are great concerns. Newer treatment methods, such as narrow-spectrum antibiotics, monoclonal antibodies, and microbial replacement therapies, are being developed and implemented. We searched PubMed to identify published literature from 2010 to 2018 using the following keywords: Clostridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 73 publications
0
65
0
1
Order By: Relevance
“…Clostridioides difficile is responsible for the majority of health-care related infections and antibiotic-associated diarrhea, with an increasing morbidity and mortality globally in the last few years (Banawas, 2018;Cho et. al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clostridioides difficile is responsible for the majority of health-care related infections and antibiotic-associated diarrhea, with an increasing morbidity and mortality globally in the last few years (Banawas, 2018;Cho et. al.…”
Section: Introductionmentioning
confidence: 99%
“…2018). Current treatment options for CDI include administration of vancomycin, fidaxomicin or metronizadol (Cho et. al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Printed with permission from Cho et al 11 Mayo Clin Proc 2020; 95: 758-769. bid, twice a day; FMT, fecal microbiota transplantation; IV, intravenously; po, orally; qid, four times a day; tid, three times a day. of 7 randomized control trials and 30 case series showed resolution of symptoms in 92% of the patients who underwent FMT.…”
Section: Introductionmentioning
confidence: 99%
“…45 In addition, standardized therapies which are enema-based (RBX2660) or capsule-based therapies (SER-109, CP101, RBX7455, VE303) are being developed. 11,14,33,[46][47][48][49][50][51][52][53] Details on these novel microbiome-based therapies are outlined in Table 3.…”
mentioning
confidence: 99%